A Ghost Proverb in Herodotus (6. 129. 4)? - Kazanskaya, Maria (Hyperboreus, 2015)
This article analyzes the status of Hippocleides’ famous retort “οὐ φροντὶς Ἱπποκλείδῃ” (Hdt. 6. 129. 4); in Herodotus’ text it is followed by the remark ἀπὸ τούτου μὲν τοῦτο ὀνομάζεται (Hdt. 6. 130. 1) which is usually understood to mean “hence the proverb”. But Herodotus’ choice of words raises a problem, as the verb ὀνομάζεσθαι was not normally used to denote popular sayings. This calls for a re-examination of the evidence that could then permit us to determine whether for the historian “οὐ φροντὶς Ἱπποκλείδῃ” was a proverb or not. The analysis of attested references to οὐ φροντὶς Ἱπποκλείδῃ in late antiquity shows that in the absolute majority of cases it is used in reference to the Herodotean context; nor does the scholarly paroemiographic tradition yield conclusive evidence. A close study of the original passage (Hdt. 6. 129–130) suggests that the exact wording of the dancing suitor’s answer, οὐ φροντὶς Ἱπποκλείδῃ, was actually invented by Herodotus (to become in later times a geﬂügeltes Wort) but that the anecdote of his unseemly behavior was well known in Herodotus’ times so that Hippocleides’ name had become “proverbial” (ὀνομάζεται).